Impact Of Balancing Grams Of Quality Protein Intake On Nutritional Status And Quality Of Life In Ckd Patients - K.L. Gupta; N. Sahni; S.V. Rana; R. Prasad; A.K. Bhalla (The Korean Society of Nephrology, 2012)
Type& amount of protein to be ingested by CKD patients in order to keep the kidneys not to deteriorate further especially in Indian population who consume mostly vegetarian diet makes planning of diet based on protein quality ratio a tough job. To analyze effect of optimizing the protein quality intake [high biological value (HBV), net protein utilization (NPU) or protein efficiency ratio (PER) of food article] on uremic toxins, nutritional status and quality of life in CKD patients consuming 0.6-0.8g/kg body wt. protein; 80% of which is from poor quality. Method: 145 predialysis CKD patients were enrolled who completed a food frequency questionnaire, quality of life (QOL) performa, nutritional status evaluation (dietary intake, anthropometry, serum albumin, total protein) before and after diet counseling [≥50%of HBV protein (from casein and egg base)]; energy 35-40 Kcal/kg body wt.). Results: Creatinine reduced significantly (p≤0.001), non significant change in blood urea& GFR improved (p≤0.01).Nutritional intake increased[good quality proteins intake ratio (p≤0.001), energy(p≤0.001)] ,BMI elevated (p≤0.01)and perception of QOL improved after diet counseling Conclusion: Judicious planning of quality protein intake within restricted quantity along with calorie optimization is critical to reduce protein waste products. Therefore, proper &timely diet counseling to combat ignorance & impart awareness to CKD patients is of utmost importance.